PEMANFAATAN CITRA QUICKBIRD DAN SISTEM INFORMASI GEOGRAFIS UNTUK IDENTIFIKASI DAERAH RAWAN KECELAKAAN Daerah Kajian: Kota Semarang, Jawa Tengah - , LINA ADI WIJAYANTI, Drs. Zuharnen, M.S. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
As one of the major cities in Indonesia, Semarang has some problems related to transport, one of them is the problem of traffic accidents. Traffic accidents can be caused due to road conditions and environment factors. The purposes of this study are: (1) Determine the ability of Quickbird imagery to identify the factors that cause traffic accidents especially road conditions and environmental factors in the main roads of Semarang, (2) Generate spatial model of traffic accidents vulnerability in the main road of Semarang in the form of maps, (3) Determine the spatial model accuracy of traffic accidents vulnerability in Semarang. This study use Quickbird imagery and and other data from related agencies to obtain information about traffic accident parameters. The field survey was conducted to test the accuracy of interpretation result. The vulnerability of the accident in this research was obtained through scoring model with weighting factor method by doing overlay upon the traffic accident parameter maps. The result of accuray for each traffic accident parameters are ranged from 73,33% to 100%. Base on the processing result, the model of traffic accident vulnerability only includes two classes, not vulnerable and vulnerable, and there are no roads includes in the very vulnerable class. The accuracy level of the model is 44%. Keywords: Accident, road, traffic